2013
DOI: 10.1071/wr12075
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in an alligator snapping turtle (Macrochelys temminckii) population

Abstract: Context Monitoring populations of long-lived species requires continuous long-term efforts. This is especially applicable for species that have experienced declines range-wide. Aims Our study assessed the current status of a population of wild Macrochelys temminckii and compared the present results to those from a survey conducted nearly a decade ago. Methods Trapping in 2010–2011 was conducted on two creeks within the refuge, during the months of May–July. Capture data were compared with data collected by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 19 publications
5
32
0
Order By: Relevance
“…The number of adults in a heavily harvested population in Louisiana was 1.1 times the number of juveniles (Boundy and Kennedy 2006). Adults in Arkansas populations (0.72:1-1.2:1; Trauth et al 1998;Howey and Dinkelacker 2013) and in an Oklahoma population (0.42:1-0.97:1; Riedle et al 2008;East et al 2013) were approximately equal to or lower than the number of juveniles. Adults in a Missouri population significantly decreased between 1993-1994 (5.2:1) and 2009 (1.2:1; Lescher et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…The number of adults in a heavily harvested population in Louisiana was 1.1 times the number of juveniles (Boundy and Kennedy 2006). Adults in Arkansas populations (0.72:1-1.2:1; Trauth et al 1998;Howey and Dinkelacker 2013) and in an Oklahoma population (0.42:1-0.97:1; Riedle et al 2008;East et al 2013) were approximately equal to or lower than the number of juveniles. Adults in a Missouri population significantly decreased between 1993-1994 (5.2:1) and 2009 (1.2:1; Lescher et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Because adults typically comprise 70% of freshwater turtle population structure (Bury 1979), and because other studies of Macrochelys have found juvenile-dominated structure, biased sex ratios, or both, we tested whether the observed ratios of adults:juveniles and males:females deviated from 1:1 with Pearson's chi-square (v 2 ) tests. Because a population of M. temminckii experienced a shift in population structure that was consistent with a population decline over a comparable time period as our study (East et al 2013), we tested for changes in size of adult males and adult females in Spring Creek across the study period using linear regression. For these analyses, we evaluated statistical significance with alpha set at 0.05.…”
Section: Population Model and Statistical Analysesmentioning
confidence: 91%
“…Mark-recapture studies permitting estimation of demographic parameters for M. temminckii have been performed at two other sites: a 2-yr study at East Fork Cadron Creek, Arkansas (hereafter, the Arkansas population, Howey et al 2013) and a 14-yr study at Sequoyah National Wildlife Refuge, Oklahoma (hereafter, the Oklahoma population; East et al 2013). To understand the comparative viability, population structure, and extinction probability of the population in Spring Creek relative to the two western populations, we input estimates of juvenile and adult female survival (phi) and population structure from the Arkansas and Oklahoma populations into the population transition model from Spring Creek and measured k, stable population structure, and generation time for the Arkansas and Oklahoma populations.…”
Section: Population Model and Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations